Long-Term Effects of Red- and Blue-Light Emitting Diodes on Leaf Anatomy and Photosynthetic Efficiency of Three Ornamental Pot Plants - Zheng, Liang; Van Labeke, Marie-Christine (Frontiers in Plant Science, 2017)
Light quality critically affects plant development and growth. Development of light-emitting diodes (LEDs) enables the use of narrow band red and/or blue wavelengths as supplementary lighting in ornamental production. Yet, long periods under these wavelengths will affect leaf morphology and physiology. Leaf anatomy, stomatal traits and stomatal conductance, leaf hydraulic conductance (Kleaf) and photosynthetic efficiency were investigated in three ornamental pot plants, namely Cordyline australis (monocot), Ficus benjamina (dicot, evergreen leaves) and Sinningia speciosa (dicot, deciduous leaves) after eight weeks under LED light. Four light treatments were applied at 100 µmol m-2 s-1 and a photoperiod of 16 hours using 100% red (R), 100% blue (B), 75% red with 25% blue (RB) and full spectrum white light (W), respectively. B and RB resulted in a greater maximum quantum yield (Fv/Fm) and quantum efficiency (ΦPSII) in all species compared to R and W and this correlated with a lower biomass under R. B increased the stomatal conductance compared with R. This increase was linked to an increasing stomatal index and/or stomatal density but the stomatal aperture area was unaffected by the applied light quality. Leaf hydraulic conductance (Kleaf) was not significantly affected by the applied light qualities. Blue light increased the leaf thickness of F. benjamina, and a relative higher increase in palisade parenchyma was observed. Also in S. speciosa, increase in palisade parenchyma was found under B and RB, though total leaf thickness was not affected. Palisade parenchyma tissue thickness was correlated to the leaf photosynthetic quantum efficiency (ΦPSII). In conclusion, the role of blue light addition in the spectrum is essential for the normal anatomical leaf development which also impacts the photosynthetic efficiency in the three studied species.